Financial regulation and risk management: addressing risk challenges in a changing financial environment - Ojo, Marianne (Munich Personal RePEc Archive, 2025)
Will the April 2nd Announcement generate its intended objectives? It’s still early days – however, it appears increasingly likely that negotiation outcomes – particularly between those significantly impacted by the Announcement, will be a major determinant in deciding whether the tariff hikes resulting from the April 2nd Announcement, will be short or long term. As of the 11th April, 2025, President Trump’s universal tariffs on China had amounted to 145% whilst China announced tariffs of 125% on U.S imports. Amongst other things, this paper aims to address complexities and challenges faced by regulators in identifying and assessing risk, problems arising from different perceptions of risk, and solutions aimed at countering problems of risk regulation. It will approach these issues through an assessment of explanations put forward to justify the growing importance of risks, well known risk theories such as cultural theory, risk society theory and governmentality theory. In addressing the problems posed as a result of the difficulty in quantifying risks, it will consider a means whereby risks can be quantified reasonably without the consequential effects which result from the dual nature of risk that is, risks emanating from the management of institutional risks.
Keywords: Financial Forecasting and Simulation; General Financial Markets; International Financial Markets; Regulation and Business Law

The effects of Basel III on the intermediation and market activities of WAEMU banks - Kouakou, Thiédjé Gaudens-Omer (University Library of Munich, Germany, 2025)
This paper analyzes the effect of Basel III adapted to WAEMU on the behavior of banks in the zone (intermediation and market activities). After having developed a model for optimizing the return on bank equity, under various constraints (balance sheet constraints, Basel III regulatory constraints), we resort to linear programming via the Danzig simplex algorithm and to a structure of reasonable rates to obtain the optimal values of the various bank balance sheet items. The results, obtained by comparing these theoretical values with the values observed before Basel III (before January 1, 2018), show an increase in the supply of loans, obtained not only from deposits and bank refinancing but also via resources from the financial markets. We can also observe the intuitive result of an increase of bank reserves in line with the constraint that Basel III imposes on banks to increase their liquidity. In short, Basel III tends to strengthen bank financing in the zone, while improving the soundness of banks through the constitution of larger reserves.
Keywords: Calibration; Credit supply; Linear programming; Prudential regulation

Biopsie de la cohabitation entre la cour commune de justice et d'arbitrage et la Cour de justice de la communauté d'Afrique de l'Est - Mbazi, Grâce Beda; Iragi Ntwali, Valéry; Cirhuza, Guillain (HAL - UPEC, 2024)
La reconnaissance simultanée des compétences judiciaires à la Cour commune de justice et d’arbitrage et à la cour de la Communauté de l’Afrique de l’Est agit comme obstacle à la réussite de l’intégration économique des pays appartenant simultanément à ces deux communautés, qui constitue pourtant un préalable fondamental en vue de leur développement. Suite à cette situation, les investisseurs pourraient se trouver dans une situation telle que des litiges tombent sous le champ d’application tant du droit de l’OHADA que de celui de la Communauté de l’Afrique de l’Est et appeler ainsi à la compétence tant de la CCJA que de la cour de justice de la CAE. Ce télescopage peut véritablement être à l'origine d'une insécurité juridique. Toutefois, pour vider les problèmes de cohabitation, la mise en œuvre d’une juridiction régionale compétente pour les affaires découlant de la mise en œuvre des Traités d’intégration régionale en Afrique serait importante. La CCJA présente dans ce sens des mérites qui peuvent être capitalisés.

Réflexion critique sur la cession des titres sociaux dans l'espace Ohada : cas de la rupture et de la nullité de la cession - Muanda Nkole wa Yahve, Don José; Grâce, Mbazi; Migani, Anciza; Bahati, Murhula; Valéry, Pacifique; Ntwali, Iragi (HAL Open science, 2023)
La cession des titres sociaux est une opération fréquente dans le monde des sociétés commerciales. L'espace des affaires OHADA ne déroge point à cette situation. Cependant, en ce qui concerne la rupture dudit contrat, le législateur communautaire prévoit une résiliation unilatérale par le cédant, sans une quelconque protection réservée au cessionnaire. De ce fait, cette procédure risquée conduit à s'interroger sur les garde-fous réservés au profit du cessionnaire, visant à sauvegarder ses intérêts et, à la limite bénéficier d'une réparation par voie de droit en termes pécuniaires du fait des préjudices subis.
Keywords: Cession; Cession titres sociaux rupture nullité espace OHADA; Espace OHADA; Nullité; Rupture; Titres sociaux

Faut-il supprimer la rupture unilatérale du contrat de vente commerciale Ohada ? - Mbazi, Grâce; Mbasoni, Séraphin; Ntwali, Valéry (HAL Open science, 2023)
Le présent article analyse la rupture unilatérale telle que prévue aux articles 280 et suivants de l'Acte uniforme révisé de l'OHADA relatif au Droit commercial général (ci-après AUDCG). Il appert de constater le fait que l'AUDCG de l'après révision a ouvert de nouvelles perspectives : une nouvelle manière de concevoir le droit à la résolution et une nouvelle technique tendant à la recherche de la gravité de l'inexécution du débiteur. Il a introduit le droit à la résolution unilatérale en instituant le critère de la gravité du comportement de la partie défaillante. Ce critère est venu remplacé celui de la privation substantielle tel que prévu dans l'ancien Acte uniforme. Malgré l'institution de la rupture unilatérale, le juge intervient ultérieurement. Il est saisi pour qu'il puisse apprécier le bien-fondé de cette dernière. Le rôle du juge est de vérifier si les conditions de la rupture étaient ou non remplies. Ainsi, le recours à la rupture unilatérale connaît certaines limites définies. Mots clés : rupture unilatérale, résolution unilatérale, critère de gravité du comportement, critère de privation substantielle, droit OHADA, Contrat de vente commerciale.

Formalisation et accès au crédit des petites et moyennes entreprises : cas du Togo - Kotoklo, Edoh; Togbenu, Fo-kossi Edem (Munich Personal RePEC Archive, 2023)
The purpose of this paper is to analyze the effect of formalization on access to credit by taking the example of Togolese (small and medium) enterprises. To achieve this objective, we test the hypothesis that the formalization of firms has a significant effect on access to credit. To do so, a Probit regression and the special regressor method were used on data from 65,725 firms extracted from the 2019 General Census of Enterprises database piloted by the National Institute of Statistics, Economic and Demographic Studies (INSEED). The results show that the variable "Formalization of enterprises (small and medium)" has a significant influence at the 1% level on the probability of access to credit. In addition, the control variables such as guarantees, cost of credit, access to the public market, gender and level of education also explain access to credit at the 1%, 1%, 5% and 10% thresholds respectively. Our results show the importance of training and capacity building for informal enterprises to formalize. Also, they will allow regulatory bodies to develop policies that can reframe the informal sector in order to contribute to the GDP and absorb more young people seeking employment.

Arbitration as a Legal Mechanism in the Settlement of Disputes under Cameroonian Law - Tambe, Hans; Forbi, Nduah Esther; Epie, Mousinga Adele (Social Science Research Network, 2021)
Recently, commercial activities in the state of Cameroon are evolving and there is an inflow of investors from within the OHADA Zone and other regions of the world to Cameroon. This has led to the proliferation of commercial contracts such as concession contracts, production sharing agreements, risk contracts between the Republic of Cameroon and foreign investors, or contracts between individuals of foreign countries as well as with Cameroonian nationals. Commonly, contracts may be breached and disagreements surface among the contracting parties. The difficulties pose is in the manner to settle such disagreements in a friendly manner to maintain the relationship between the parties and to enables the contracting parties to resolve the disputes more cost-effectively and increase business efficiency in Cameroon. However, the state of Cameroon has a favorable attitude towards bilateral and multilateral investment treaties to guarantee protection to investors in the territory. This elucidates the reason why the government of Cameroon has enacted laws and ratified regional and international treaties, aimed at safeguarding a smooth atmosphere for investors and other commercial traders particularly in the domain of arbitration to help in resolving disputes in case of any disagreement among contracting parties. This article will present the authorities involved in arbitration with the experience regarding the application of the various law and institutions concerned with the arbitration. This will also help contracting parties or investors to understand the legal mechanisms in the settlement of disputes through arbitration in Cameroon.
Keywords: Arbitrage; Arbitragem; Arbitration; dispute; legal; mechanism; settlement

Legal Protection of Foreign Direct Investment in the OHADA Area - Ngoya, Dominique (Social Science Research Network, 2021)
This paper analyzes the protection of Foreign Direct Investments in the OHADA area, specifically, its regulation by the Treaty of Organization and Harmonization in Africa of Business Law (OHADA Treaty). It is to restore legal and judicial security within their scope that OHADA member countries have undertaken to harmonize and unify their economic sector legislation to attract foreign investment as a factor in economic development. Several national and international legal instruments are responsible for the protection of foreign direct investment in OHADA countries. Indeed, the volume of foreign direct investment (FDI) to developing countries increased considerably during the 1990s; As Africa is now one of the favorite destinations for Western and even African investors, it is becoming a very profitable continent for investors. However, the issue of regulating or securing foreign investment in African countries is still flawed. The establishment of OHADA, in a way, is in the same direction; if we stick to the purpose of the organization prescribed in paragraph 5 of the preamble to the OHADA Treaty, which states that the purpose of the OHADA law is to "promote the growth of economic activity and encourage investment." Unfortunately, this objective remains only an announcement of the preamble to the Treaty, because of the definition of business law given by Article 2 of that treaty. However, the list of subjects is not exhaustive, investment remains absent. Thus, foreign investment is not regulated by the OHADA Treaty, so even investment-related activities are held by other subjects (corporate law, commercial law, and security law). The omission of FDI in the scope of the OHADA Treaty leads us to raise the question of its regulation.This work proposes a reflection that the OHADA Treaty should be modernized through reform including investment and many other issues to deal effectively with the issue of foreign investment given the ineffectiveness of national and sub-regional instruments in this area.
Keywords: Foreign direct investment; Investment Law; Investment Protection; OHADA

The Effectiveness of the Harmonization Tool Adopted Under the Ohada Regime - Ceesay, Buba (Social Science Research Network, 2020)
The Organization for the Harmonization of Business Law in Africa, OHADA, is a regional entity whose primary objective is to harmonize the Business Law of its members. It has adopted legislative measures and institutional setups to ensure the realization of this object. This paper critically examined the effectiveness of the harmonization tool adopted under OHADA. The paper first gives a brief overview of OHADA setups, then the advantages and shortcomings of the harmonization tool adopted under the OHADA regime and finally concluded that though OHADA is a major step towards the attainment of harmonization of business law and Integration with the view of fostering development and business activities, its harmonization tool is lacking full efficacy towards the attainment of the objectives of the organization due to prevailing limitations and challenges.
Keywords: SSRN